2018
DOI: 10.1007/s10926-018-9804-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Return to Work 12 Months After Solid Organ Transplantation: Results from the Swiss Transplant Cohort Study

Abstract: Background Return to work with or after a chronic disease is not a very well understood process, influenced by a variety of personal, professional, societal and medical factors. The aim of this study is to identify predictors for return to work 12 months after a solid organ transplant applying a bio-psycho-social model. Methods This study is based on patients included in the Swiss Transplant Cohort Study, a national prospective multicentre cohort, who underwent a first solid organ transplant (kidney, liver, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
5
21
0
Order By: Relevance
“…The authors consider this result to be comparable with other countries, as Krivchenia et al estimated that 5-year salaried work was possible for 48% of the CF patients undergoing transplantation [12]. Pre-transplant employment seems to be one of the most important factors when it comes to returning to work after lung transplantation [5,7]. What is more, it is also an important factor of rejoining the workforce after liver transplantation [13].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The authors consider this result to be comparable with other countries, as Krivchenia et al estimated that 5-year salaried work was possible for 48% of the CF patients undergoing transplantation [12]. Pre-transplant employment seems to be one of the most important factors when it comes to returning to work after lung transplantation [5,7]. What is more, it is also an important factor of rejoining the workforce after liver transplantation [13].…”
Section: Discussionsupporting
confidence: 56%
“…Resuming or finding employment after becoming a graft recipient is just another measure of successful treatment. A Swiss transplant cohort study presented by Vieux et al [7] assessed the prospects of employment after the first solid organ transplantation (kidney, liver, heart or lung). The authors estimated that 49.8% of the studied recipients were employed 12 months after receiving the graft [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the group of men, the important factor determining employment after transplantation was the transplanted organ. Kidney patients being more likely to be employed after transplantation than non-kidney patients was also observed in other studies 10 11. Some authors indicated that the possible cause of this is longer experience with kidney transplantation compared with liver, heart or lung transplantation, or more complications observed in non-kidney recipients after surgery, hindering them from work 10 15 20…”
Section: Discussionmentioning
confidence: 65%
“…For instance, educational level and household income have been studied as risk factors for, respectively, sleep quality 34 and new-onset obesity. 35 Other studies have named pre-transplant employment status as a predictor of better post-transplant health (with health levels assumed based on post-transplant employment status) [36][37][38] ; however, prospective, reliably measured indicators of care deprivation-essential tools to identify the full impact of socioeconomic status on general and transplant-specific long-term health outcomes-are lacking. 33 The measurements of the Swiss Transplant Cohort Study (STCS), 39,40 a nationwide open cohort study, cover the SAI's variables, along with subsequently assessed outcomes.…”
Section: Introductionmentioning
confidence: 99%